The Role of DNA Methylation in Ischemic Stroke: A Systematic Review - Zeng, Minyan; Zhen, Juanying; Zheng, Xiaodan; Qiu, Hongyan; Xu, Xiaonan; Wu, Jun; Lin, Zhijian; Hu, Jun (Frontiers in Neurology, 2020)
Background: Knowledge about the classic risk and protective factors of ischemic stroke is accumulating, but the underlying pathogenesis has not yet been fully understood. As emerging evidence indicates that DNA methylation plays a role in the pathological process of cerebral ischemia, this study aims to summarise the evidence of the association between DNA methylation and ischemic stroke. Methods: MEDLINE, EMBASE, PubMed and Cochrane Central Register of Controlled Trials were searched for eligible studies. The results reported by each study were summarised narratively. Results: A total of 20 studies with 7014 individuals finally met the inclusion criteria. Three studies focused on global methylation, 11 studies on candidate-gene methylation, and six on epigenome-wide methylation analysis. Long-interspersed nuclear element 1 was found to be hypomethylated in stroke cases in two studies. Another 16 studies reported 37 genes that were differentially methylated between stroke cases and controls. Individuals with ischemic stroke were also reported to have higher acceleration in Hanuum ’s epigenetic age compared to controls. Conclusion: DNA methylation might be associated with ischemic stroke and play a role in several pathological pathways. It is potentially a promising biomarker for stroke prevention, diagnosis and treatment, but the current evidence is limited by sample size and cross-sectional or retrospective design. Therefore, studies on large asymptomatic populations with the prospective design are needed to validate the current evidence, explore new pathways and identify novel risk/protective loci.